2016
DOI: 10.1080/15685551.2016.1231046
|View full text |Cite
|
Sign up to set email alerts
|

pH responsive alginate polymeric rafts for controlled drug release by using box behnken response surface design

Abstract: Aim of the present work was to develop alginate raft forming tablets for controlled release pantoprazole sodium sesquihydrate (PSS). Box behnken design was used to optimize 15 formulations with three independent and three dependent variables. Physical tests of all formulations were within pharmacopoeial limits. Raft was characterized by their strength, thickness, resilience, acid neutralizing capacity, floating lag time and total floating time. Raft strength, thickness and resilience of optimized formulation A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…The TFT of all prepared formulations ranged from 5-6 hours. Abbas et al 10 observed a similar pattern of FLT and TFT of alginate raft forming formulations.…”
Section: Floating Lag Time (Flt) and Total Floating Time (Tft)mentioning
confidence: 72%
See 2 more Smart Citations
“…The TFT of all prepared formulations ranged from 5-6 hours. Abbas et al 10 observed a similar pattern of FLT and TFT of alginate raft forming formulations.…”
Section: Floating Lag Time (Flt) and Total Floating Time (Tft)mentioning
confidence: 72%
“…Antacids are also trapped in the polymeric gel to extend the neutralization time. 10 The antacids in the formulation immediately neutralize the acid in the stomach and reduce the burning sensation. A raft was effectively formed on the surface of the SGF when adding tablets of formulations PPR1 to PPR5, but a raft did not develop when adding formulations PPR6 to PPR9.…”
Section: Chemical Properties Of Raftmentioning
confidence: 99%
See 1 more Smart Citation
“…Where Y is the measured response of the dependent variables, β0 is the intercept, β1-β9 are the regression coefficients computed from the observed experimental values of Y. X1, X2 and X3 are the coded value of the independent variables. X1 X2X3 (a, b = 1, 2, 3) and X 2 i (i = 1, 2, 3) represent the interaction and quadratic terms, respectively [16,17]. The graft copolymer of karaya with acrylamide was characterized by FTIR, DSC, XRD and SEM and % grafting (%G) and % grafting efficiency (%GE) were calculated by using following equations [18]:…”
Section: Experimental Designmentioning
confidence: 99%
“…The physicochemical properties of sodium alginate, the sodium salt of alginic acid, indicate that this natural macromolecule is biodegradable, nontoxic and pH sensitive in nature; in addition, the pH sensitivity of the polymer makes it stable only in an acidic environment, while in alkaline media, rapid dissolution occurs, which leads to instability and limits its applications. Sodium alginate swells in water but typically produces an acid pH gel due to its protonation and can be crosslinked by the application of physical and chemical methods [1]. The chemical structure of alginate, as mentioned in Fig.…”
Section: Introductionmentioning
confidence: 99%